Finding Victims of Human Trafficking, 2005-2008 (United States) - Newton, Phyllis J. ([Verlag nicht ermittelbar], 2015)
This study was a response to the Trafficking Victims Protection Reauthorization Act passed by Congress in 2005, which called for a collection of data; a comprehensive statistical review and analysis of human trafficking data; and a biennial report to Congress on sex trafficking and unlawful commercial sex acts. It examined the human trafficking experiences (and to a lesser extent commercial sex acts) among a random sample of 60 counties across the United States. In contrast to prior research that had examined the issue from a federal perspective, this study examined experiences with human trafficking at the local level across the United States. The specific aims of the research were to: Identify victims and potential victims of domestic labor and sex trafficking; Determine whether they have been identified as victims by law enforcement; and Explore differences between sex trafficking and unlawful commercial sex. To achieve these goals the researchers collected data through telephone interviews with local law enforcement, prosecutors, and service providers; a mail-out statistical survey completed by knowledgeable officials in those jurisdictions; and an examination of case files in four local communities. This latter effort consisted of reviewing incident and arrest reports and charging documents for a variety of offenses that might have involved criminal conduct with characteristics of human trafficking. Through this method, the researchers not only gained a sense of how local authorities handled these types of cases but also the ways in which trafficking victims "fall through the cracks" in the interfaces between local and federal judicial systems as well as among local, state, and federal law enforcement and social service systems.